2016
DOI: 10.1021/acs.jpclett.6b02451
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Unconventional Hydrogen Bonds in Determining BII Propensities in B-DNA

Abstract: An accurate understanding of DNA backbone transitions is likely to be the key for elucidating the puzzle of the intricate sequence-dependent mechanical properties that govern most of the biologically relevant functions of the double helix. One factor believed to be important in indirect recognition within protein-DNA complexes is the combined effect of two DNA backbone torsions (ε and ζ) which give rise to the well-known BI/BII conformational equilibrium. In this work we explain the sequence dependent BII prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 41 publications
2
24
0
Order By: Relevance
“…The four oligomers studied in this work are listed in Table 1 . These oligomers were chosen so as to include pyrimidine-p-purine (YpR) and purine-p-purine (RpR) steps that have already been shown to be able to exist in high and low twist states ( 28 , 43 , 44 ). Table 1 lists the presence of these steps within the segment of each oligomer that will be subjected to twist restraints (namely, base pairs 3–15).…”
Section: Resultsmentioning
confidence: 99%
“…The four oligomers studied in this work are listed in Table 1 . These oligomers were chosen so as to include pyrimidine-p-purine (YpR) and purine-p-purine (RpR) steps that have already been shown to be able to exist in high and low twist states ( 28 , 43 , 44 ). Table 1 lists the presence of these steps within the segment of each oligomer that will be subjected to twist restraints (namely, base pairs 3–15).…”
Section: Resultsmentioning
confidence: 99%
“…Segments storing more elastic energy also exhibit significant transitions in the backbone structure (Fig 7 and S11-S31 Figs in S1 File). Since, C/G segments exhibit a higher propensity for adopting a BII state in unrestrained DNA [12,44,45,46] these segments have also a higher capacity towards transitions from BII to BI states (which overall relaxes unwinding stress, see previous paragraphs). Especially, at high supercoiling (before melting) significant increase in the BI propensity is observed along the DNA sequences mostly in the G/C-rich segments (orange bars in Fig 7, see also Fig 8).…”
Section: Plos Onementioning
confidence: 99%
“…In previous Molecular Dynamics (MD) simulation and NMR based studies, the sequence dependent population of BI/BII states and their impact on DNA’s structure has been extensively investigated (13–18). Recently, the sequence dependence of BI/BII states was systematically analyzed using trajectories obtained by the Ascona B-DNA consortium (ABC) based on a database of extensive MD simulations of DNA oligomers containing all 136 distinct tetranucleotide sequences (15,19). It was found that the sequence dependent formation of unconventional hydrogen bonds between base and backbone atoms plays a key role in stabilizing the BII substate (a C8-H8..O3′, between purine base and backbone in case of RpR and YpR steps; and a C6-H6..O3′ contact in RpY and YpY steps(15,19)).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the sequence dependence of BI/BII states was systematically analyzed using trajectories obtained by the Ascona B-DNA consortium (ABC) based on a database of extensive MD simulations of DNA oligomers containing all 136 distinct tetranucleotide sequences (15,19). It was found that the sequence dependent formation of unconventional hydrogen bonds between base and backbone atoms plays a key role in stabilizing the BII substate (a C8-H8..O3′, between purine base and backbone in case of RpR and YpR steps; and a C6-H6..O3′ contact in RpY and YpY steps(15,19)). The formation of a (base) C-H..O3′ (sugar) hydrogen bond contact perfectly correlated with the formation and percentage of BII states at dinucleotide steps in DNA.…”
Section: Introductionmentioning
confidence: 99%